The effect of ZrOx modification of graphene nanoribbon on its adsorption for NOx: A DFT investigation - Ahmad I. Ayesh (10188469) (2022)
Emission of anthropogenic short-lived gases that are chemically reactive including NOx (x=1 and 2) and CO has a well-known influence on altering the climate chemistry of the troposphere layer, and hence the abundance of many greenhouse gases such as HFCs, O3, and CH4. Therefore, the progress in production of exceedingly selective gases detectors to monitor and control their content in the ambient is crucial to track their emission. The effect of alteration of graphene nanoribbon of armchair structure (AGNR) by zirconium (Zr) metal as well as its oxides on the adsorption for NOx gases is examined is this work. First principles density functional theory computations (DFT) are employed to explore the adsorption energy (Ed) and length (D), band structure, charge transferred (ΔQ) as well as density of states (DOS) of pure and modified AGNR structures using ZrOx where x=0,1, and 2. Herein, ZrOx is introduced to AGNR by two pathways: doping (substitution of carbon atom(s)), and decoration (addition on top of surface). The outcomes of this study demonstrate extraordinary improvement of NOx adsorption on the modified AGNR structures. Though the adsorption energy of NOx gas is boosted, generally, for AGNR structures due to modification with ZrOx, the doped structures have greater adsorption energy when compared with the decoration ones. The highest adsorption energy for NOx gases is for AGNR doped using ZrO2, followed by that for AGNR doped using ZrO. Herein, the adsorption energy of AGNR doped using ZrO2 for NO increases 26.9 times while it increases 19.6 times for NO2 as compared with those of the pure structure. Hence, modified AGNR structures using ZrOx may be implemented for applied field sensors for environmental applications to detect and control NOx emission. Other Information Published in: Materials Chemistry and Physics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.matchemphys.2022.126693